Project management ROI a step-by-step guide for measuring the impact and ROI for projects - Phillips, Jack J., 1945-; Brantley, Wayne; Phillips, Patricia Pulliam; ProQuest (firma) (Hoboken, N.J. : Wiley, 2012)
"Often organizations looking to implement project management have great difficulty justifying their expenditures on training, personnel, processes, systems, and software. This book will provide the methodology and tools developed by Jack Phillips and the ROI Institute which are needed by organizations to gather data that can be used to justify their capital investments into project management. The research conducted will allow them to justify their investments. The Philips methodology has become the defacto ROI methodology for evaluating training and company initiatives. Deployment of this methodology for evaluating the value of project management is invaluable for the project management community. This will justify to senior executives the strategic value that they will realize from their investment into project management. The book will follow PMI's PMBOK and will also provide real world cases of both successful and not-so-successful project management ROI"--
Machine generated contents note: Preface.Acknowledgments.About the Authors.Chapter 1. Project Management Issues and Challenges.Chapter 2. The Project Management Life Cycle.Chapter 3. ROI Methodology Basics.Chapter 4. Achieving Business Alignment with the Project.Chapter 5. Measuring Reaction and Learning.Chapter 6. Measuring Application and Implementation.Chapter 7. Measuring Business Impact.Chapter 8. Isolation of Project Impact.Chapter 9. Converting Data to Money.Chapter 10. Measuring the Intangibles.Chapter 11. Monitoring Project Costs and Calculating ROI.Chapter 12. Forecasting Value, Including ROI.Chapter 13. Reporting Results.Chapter 14. Implementing and Sustaining ROI.Notes.Index.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Project management; Project management -- Evaluation; Rate of return; Human capital; elektronické knihy; electronic books